Fatigue Performance of Titanium Alloy Welded Joints. Issue 2 (February 2021) - Zhang, Lijun; Kang, Jingjie; Tang, Shengming; Shi, Xiumei; Sun, Yuandong; Wang, Ruolan; Li, Shengjie
Abstract: Titanium alloys are widely used in aerospace, chemical engineering and medicine because of their excellent tensile, fatigue strength and corrosion resistance. For aerospace titanium alloys, fatigue performance is an important parameter, especially as a structural material. Welding is an indispensable method. After welding, there is a large unevenness in the structure and mechanical properties of the welded joint. Fatigue performance also has a profound effect. This article has done a deep research on the fatigue performance of titanium alloy welded streets, using ANSYS software to calculate and analyze the stress concentration of welded joints, observe and analyze the welding defects on fatigue fractures, and discuss the effect of welding defects on fatigue behavior The equivalent residual stress after spot welding at the center of the joint weld obtained by conventional laser welding near the welding end position is 547 MPa, of which the longitudinal residual stress along the weld direction is tensile stress, the magnitude is 482 MPa, and the transverse direction perpendicular to the weld direction The residual stress is a compressive stress of 114.0 MPa, and the equivalent residual stress of the weld is reduced after the use of SGCW technology. The equivalent residual stress at this point is reduced to 489 MPa, which is a reduction of nearly 12%.